Health Education for Pregnant Women on Exclusive Breastfeeding in Aek Haruaya Village - Ica Fauziah Harahap; Riska Yanti; Rina Marlina Hutasuhut (International Journal of Community Service (IJCS), 2026)
Exclusive breastfeeding for the first six months of life is a critical public health strategy to ensure optimal growth, development, and survival of infants, yet coverage in Indonesia remains below global targets. Pregnant women are a strategic target group for breastfeeding counseling because knowledge, attitudes, and social support formed during pregnancy strongly influence later feeding practices. This analytical survey with a cross-sectional design was conducted as part of a community-based health education program in Aek Haruaya Village, Portibi District, North Padang Lawas Regency, Indonesia, in 2026. A total of 39 pregnant women participated in a structured counseling session on the definition, benefits, and correct practice of exclusive breastfeeding, followed by an assessment of maternal knowledge. Post-education, 51% of respondents demonstrated good knowledge and 49% demonstrated sufficient knowledge regarding exclusive breastfeeding, indicating that most participants reached at least a moderate level of understanding. The activity was well received and highlighted persistent gaps in prior exposure to breastfeeding education among pregnant women in the village. The findings support integrating systematic health education on exclusive breastfeeding into routine antenatal services in rural areas to strengthen mothers’ knowledge and contribute to increasing exclusive breastfeeding coverage.